The aging lysosome: an essential catalyst for late-onset neurodegenerative diseases - Nixon, Ralph A. (Biochim Biophys Acta Proteins Proteom, 2020)
Lysosomes figure prominently in theories of aging as the proteolytic system most responsible for eliminating growing burdens of damaged proteins and organelles in aging neurons and other long lived cells. Newer evidence shows that diverse experimental measures known to extend lifespan in invertebrate aging models share the property of boosting lysosomal clearance of substrates through the autophagy pathway. Maintaining an optimal level of lysosome acidification is particularly crucial for these anti-aging effects. The exceptional dependence of neurons on fully functional lysosomes is reflected by the phenotypes seen in congenital lysosomal storage disorders, which commonly present as severe neurodevelopmental or neurodegenerative conditions even though lysosomal deficits are systemic. Similar connections are now being appreciated between risk for late age-onset neurodegenerative disorders and primary lysosomal deficits. In diseases such as Alzheimer’s and Parkinson’s, as in aging alone, primary lysosome dysfunction due to acidification impairment is emerging as a frequent theme, supported by the growing list of familial neurodegenerative disorders that involve primary vATPase dysfunction. The additional cellular roles played by intraluminal pH in sensing nutrient and stress and modulating cellular signaling have further expanded the possible ways that lysosomal pH dysregulation in aging and disease can disrupt neuronal function. Here, we consider the impact of cellular aging on lysosomes and how these changes may create the tipping point for disease emergence in major late-age onset neurodegenerative disorders.